A dialética entre redes e grupos no campo da comunicação midiática na Amazônia - CASTRO, Fábio Fonseca de (Pontíficia Universidade Católica do Rio de Janeiro, 2022)
The article attempts, first, a mapping of networks and communication groups present in the brazilian Amazon region. It seeks to discuss, from this mapping, some conflicts of interest present in the relations between local groups and the national communication networks. Our intention is to demonstrate the hegemonic microdisputes present in this relationship, discussing the limitations in the interpretation of the systemic model of communication networks while vertical flow, characterized by regularity of power relationships.